CSR Practices in India: Way Ahead (Journal of Informatics Education and Research, 2024)
Corporate Social Responsibility (CSR) has become a critical part of corporate behavior, with businesses worldwide recognizing their respective role and part in addressing social, economic, and environmental challenges. Corporate Social Responsibility (CSR) in India has evolved significantly in recent years, driven by legislative changes, stakeholder expectations, and global trends. This paper explores the current landscape of CSR practices in India, analyzing the impact of the Companies Act, 2013, which mandates CSR activities for certain companies. The study examines the effectiveness of CSR initiatives, the challenges faced by corporations, and the role of various stakeholders in shaping CSR practices. Through a comprehensive review of literature and case studies, the paper identifies best practices and provides recommendations for enhancing CSR activities to achieve sustainable development goals. The findings suggest that while significant progress has been made, there is a need for more strategic alignment of CSR activities with core business objectives and a greater emphasis on measuring social impact.